2015
DOI: 10.1590/1983-40632015v4536869
|View full text |Cite
|
Sign up to set email alerts
|

Épocas de semeadura, cultivares e densidades de plantas para algodão adensado em segunda safra

Abstract: RESUMO O cultivo de algodoeiro adensado em segunda safra, em ambiente não irrigado, após soja ou feijão, tem aumentado no Cerrado do Centro-Oeste brasileiro. Com essa mudança de época de semeadura, as plantas de algodão estão mais expostas a condições climáticas adversas. Objetivou-se avaliar o efeito de cultivares, densidades de plantas e épocas de semeadura sobre a produção de algodão. Os experimentos foram realizados em três anos consecutivos. Em cada ano, os tratamentos foram constituídos por duas épocas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
1
4
0
9
Order By: Relevance
“…In general, it is verified that the later the planting of the cotton takes place, the lower the yields obtained by the genotypes are. Similar results were found in studies by Ferreira et al (2015), which analyzed sowing in the second fortnight of January and the first fortnight of February of a three-year harvest, and found that late sowing reduces lint yield by 25%, 17% and 41% in the years studied. Carvalho et al (2011) also verified higher productivity of cotton seed when cotton was sown at the end of December in contrast to sowings in January and February.…”
Section: Contentssupporting
confidence: 87%
See 1 more Smart Citation
“…In general, it is verified that the later the planting of the cotton takes place, the lower the yields obtained by the genotypes are. Similar results were found in studies by Ferreira et al (2015), which analyzed sowing in the second fortnight of January and the first fortnight of February of a three-year harvest, and found that late sowing reduces lint yield by 25%, 17% and 41% in the years studied. Carvalho et al (2011) also verified higher productivity of cotton seed when cotton was sown at the end of December in contrast to sowings in January and February.…”
Section: Contentssupporting
confidence: 87%
“…In the definition, the agricultural zoning takes into account the environmental conditions favorable to the good development of the crop, highlighting the sowing season. The correct season should provide higher productivity and better fiber quality, in order to avoid possible adverse climatic phenomena, such as droughts, low temperatures and rainfall in the harvest (AMORIM NETO et al, 1997. In Minas Gerais State, cotton is traditionally sown in the months of November to December and harvested between June and July (FERREIRA et al, 2015), as the crop finds climatic conditions favorable to its development, such as temperatures ranging from 20ºC to 30ºC in the summer and precipitations that vary between 700 and 1500 mm, ideal to complete its cycle (BELTRÃO et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al (2012) studied the effects of different row spacing and plant densities on fiber productivity and found that only spacing between rows had a significant effect. Working with cultivars in different densities, Ferreira et al (2015) found that the interaction between cultivar and density was not significant. Moreover, according to these authors, the availability of water in the soil markedly influenced the responses of cotton plants to plant density.…”
Section: Resultsmentioning
confidence: 97%
“…In years with an adequate distribution and amount of rainfall during the cycle, it has been found that cotton can be grown in a second crop, with a population of 178,000 plants ha -1 . However, if low rainfall or water deficits during the reproductive development of cotton have been forecasted, populations of 132,000 plants ha -1 can be expected (Ferreira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This practice occurs almost simultaneously with the soybean harvest as a primary crop. The average productivity of Brazilian cotton has grown due to the use of more productive cultivars, greater processing yield and fertilizer programs (FERREIRA et al, 2015), as the application of micronutrients.…”
Section: Introductionmentioning
confidence: 99%